A clinicomycologic study of onychomycosis at a tertiary health-care center in Chennai - Chandan Ashokan; Aditya Kumar Bubna; Anandan Sankarasubramaniam; Mahalakshmi Veeraraghavan; Sudha Rangarajan; Adikrishnan Swaminathan (Wolters Kluwer Medknow Publications, 2017)
Background: Onychomycosis poses to be an important public health problem. There has been a worldwide increase in the prevalence of onychomycosis with factors such as diabetes mellitus, poor peripheral circulation, indulgence in sporting activities, and prolonged antibiotic usage playing major contributory roles. Further, management of fungal infections of nails usually requires a prolonged course with a tendency for relapse. Aim: To study the clinical, epidemiologic, and demographic profile of onychomycosis and determine various organisms responsible for the same. Methods: A cross-sectional study was done over a 1-year period, wherein after patient enrollment, a thorough clinical evaluation was performed, followed by microscopically examining the infected nail specimen under 40% potassium hydroxide, which was succeeded by cultivating the organisms on fungal culture media and identifying the pathogen both by closely studying colony morphology in culture and also microscopically utilizing lactophenol cotton blue staining. Results: Females (67.3%) were more commonly affected than males (32.7%). The most common age group affected was 20-40 years(47%). Majority of patients demonstrated both finger and toe nail involvement (43.6%). Distal and lateral subungual onychomycosis (55.4%) was the most common clinical variant of onychomycosis identified in our study. Out of the 101 patients in our study, 86 demonstrated a positive fungal growth on culture. Non-dermatophyte moulds (NDM) (58.1%) were the most common fungal isolate followed by Candida species (36%) and dermatophytes (5.8%). Conclusion: Unlike most studies, NDM constituted the major pathogen among our participants.